Day 1 -1630 - John Fairweather.pdf - Gill, Philip (Cranfield University, 2023)
Developments in dense Nitrocellulose Nitration John Fairweather - Bowas-Induplan Chemie Ges.m.b.H. 9th International Nitrocellulose Symposium Presentations
Keywords: 'nitrocellulose'